NASKAH MELAYU DIGITAL: SEBUAH INOVASI SUMBER KAJIAN PENDIDIKAN ISLAM BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) - Ellya Roza; Mudasir Mudasir (POTENSIA: Jurnal Kependidikan Islam, 2019)
This paper aims to find out the digital Malay manuscript as a source of studies in the field of Islamic education. Malay manuscript is one of the nation's documents written manually using Arabic-Malay characters and in Malay. This means that the Malay manuscript is a stroke of the local genius of the nation and is an intellectual icon of the people of his day. But along with advances in technology, the Malay manuscript also experienced development through this technology by means of digitalization. In terms of methodology, this paper is a study of historical and cultural heritage involving Malay manuscript, so this study uses descriptive qualitative methods that are linked to analysis and interpretation and finally focuses on content analysis. At the end of the study it was found that in addition to the Quran and Hadith which are the sources of Islamic education studies, it turns out that the digital Malay manuscript can be used as the next source, because the Malay manuscript is a legacy of cultural heritage that is loaded with noble values of life such as social, political, religious, educational, culture, economics, language, literature and so on. Therefore, digital Malay manuscript is an ICT-based innovation that can be used as a source of study of Islamic education. Digital Malay manuscripts are very easy to obtain because in various places where Malay manuscripts have been digitalized, scientists can use them. In addition, digital Malay manuscripts can be accessed through the internet with various sites.